Anasarca, steatorrhea, and hypoalbuminemia 18 years after total gastrectomy: a case report - Yu Igata; So Okubo; Yu Ohkura; Masaki Ueno; Harushi Udagawa (Surgical Case Reports, 2019)
Abstract Background Pancreatic exocrine insufficiency (PEI) is known to occur after total gastrectomy. We experienced a case of PEI occurring 18 years after surgery, leading to a potentially fatal condition of capillary leak syndrome (CLS). Case presentation The case is a 58-year-old man on a healthy diet who underwent total gastrectomy 18 years before. He was admitted for a 3-month history of anasarca, steatorrhea, and hypoalbuminemia. An episode of fever occurred during workup, followed by pulmonary edema and shock. The patient was transferred to the intensive care unit and was started on fluid management with albumin infusion. A multidisciplinary team meeting was held, and a clinical diagnosis of PEI resulted in CLS was made and we started administration of oral pancrelipase to show clinical improvement. The patient was discharged, and he remained asymptomatic for 13 months. Conclusion In a post-gastrectomy patient with malnutrition, PEI should be suspected regardless of the period since surgery. When recognized, immediate replenishment of albumin and pancreatic enzymes should be initiated to prevent clinical deterioration.